Modelagem do desenvolvimento e produtividade de batata-doce - Erpen, Lígia (2013)
The objectives of this dissertation were to determine the cardinal temperatures of sweet potato and compare the simulation of node appearance with the plastochron model (linear) and with Wang and Engel model (nonlinear) and the best way input air temperature in the models and to assess the effect of planting dates on tuber initiation and storage root yield of sweet potato in a subtropical environment. Models calibration and the test were with data of number of nodes on the main stem of sweet potato plants, collected at seven planting dates in 2010, 2011 and 2012 growing seasons. The tuber initiation and storage root yield were assessed in an experiment with four planting dates in 2011 and 2012 growing seasons. The experiments were conducted in the experimental area of the Department of Plant Science, UFSM, Santa Maria, RS, with cultivar Princesa at planting density of de 25.000 plants ha-1. The experiment was a complete randomized block design with four replications. The version with mean temperature was superior to the version with the minimum and maximum temperature as input in both models. The plastochron and Wang and Engel models showed similar performance, with RMSE ranging from 2.1 to 2.2 nodes respectively. Both models can be used to simulate the development of sweet potatoes when it is cultivated in the recommended period. Outside this period is suggested to use the model of Wang and Engel. The conditions of temperature and photoperiod modified the tuber initiation in each planting date, indicating that short photoperiods accelerate its occurrence. The storage root yield was higher when planting was done in late winter due to the longer duration of tuber bulking which coincided with periods of high solar radiation and temperatures favorable to the growth and development of sweet potato. Keywords: Ipomoea batatas. Phenology. Modeling. Planting dates.